Pembinaan Ketaatan Beribadah dan Kedisiplinan Belajar pada Siswa di SMK Muhammadiyah Salatiga Tahun Ajaran 2023/2024 - Wati, Irma Hajjar; Purnomo, Purnomo (Pacsasarjana UIN Sultan Syarif Kasim Riau, 2024)
This research aims to determine strategies for fostering devotion to worship and discipline in learning, supporting factors, and inhibiting factors in fostering devotion to worship and discipline in learning in students at SMK Muhammadiyah Salatiga for the 2023–2024 academic year. This research includes field research using qualitative research methods. The data obtained came from primary data in the form of interviews with the principal, PAI teachers, and students, as well as secondary data in the form of observations and documentation. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions (verification). Checking the validity of the data uses source triangulation and technical triangulation. The results of this research show that: (1) the strategy for fostering obedience to worship in students is carried out through providing understanding, habituation, guidance, monitoring, and supervision. (2) The supporting factors are students' self-awareness, the cooperation of the school principal with all teachers, facilities and infrastructure that are adequate, and assistance for students. (3) The inhibiting factor is the social environment (friends). (4) The strategy for fostering learning discipline in students is carried out through building and familiarizing students with a disciplined learning attitude, teacher class management, the provision of adequate learning support tools, governance orderliness related to learning, and assessment. (5) Supporting factors are teacher discipline, support from the principal and all teachers, and a conducive classroom environment. (6) Inhibiting factors are students' attitudes towards lessons and mass media (cellphones).